Industrial inheritances: Makers, relatedness and materiality in New York and Chicago. Issue 11 (2nd November 2019) - Eisenburger, Max; Doussard, Marc; Wolf-Powers, Laura; Schrock, Greg; Marotta, Stephen
ABSTRACT: As policy-makers and advocates seek to harness the 'Maker movement' for regional innovation and economic development, attention is turning to the role of regional 'entrepreneurial ecosystems' in supporting Makers' growth potential. Through interviews with 92 Maker enterprises across three industry subsectors in two regions, the paper demonstrates how the materiality of manufacturing processes, products and end markets influences Makers' growth trajectories, and their effects on the role of regional agglomeration economies. This adds an important material dimension to ongoing academic discussions of industry relatedness focused principally on knowledge transfer, and further suggests that targeted industrial retention may complement manufacturing entrepreneurship policies.